1999
DOI: 10.1136/bjo.83.2.219
|View full text |Cite
|
Sign up to set email alerts
|

Long term ultrastructural changes in human corneas after tattooing with non-metallic substances

Abstract: Aim-To investigate the ultrastructural appearance and the deposition pattern of dye particles in long term non-metallic corneal tattooing. Methods-Two tattooed human corneas were obtained by keratoplasty. One corneal button was fixed in Karnovsky's solution and the other in Trumps' solution. Both corneas were divided and processed for conventional light (LM) and transmission electron microscopy (TEM). Five additional formalin fixed corneas with tattoos were retrieved from paraYn for TEM. The time between tatto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
5

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 7 publications
1
22
0
5
Order By: Relevance
“…5 They concluded that keratocytes can actively ingest and retain particles of nonmetallic dyes within their cell membranes for a very long period of time. Fujita and co-workers experimentally showed that rabbit corneal fibroblasts can endocytose particles of injected India ink within 3-4 days and keep them for at least 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…5 They concluded that keratocytes can actively ingest and retain particles of nonmetallic dyes within their cell membranes for a very long period of time. Fujita and co-workers experimentally showed that rabbit corneal fibroblasts can endocytose particles of injected India ink within 3-4 days and keep them for at least 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Essa observação foi por nós constatada pela manutenção do aspecto cosmético da córnea após 1 ano de seguimento (8) . A segurança do transplante lamelar associado a tatuagem é relativamente alta, pelo que já foi publicado em relação aos pigmentos (2,4) e por se tratar de transplante lamelar, realizado sem a abertura do globo ocular. A toxicidade dos pigmentos merece mais estudos (1) , mas se sabe que pigmentos não metá-licos (ex: tinta da índia, como o que foi utilizado no caso descrito) são fagocitados pelos ceratócitos e aparentemente apresentam menor toxicidade e maior tempo de retenção na córnea do que pigmentos metálicos (2) .…”
Section: Discussionunclassified
“…Não descartamos o quadro de hiperemia persistente ser decorrente de alguma manifestação tóxica do pigmento. Porém, baseado em outros estudos publicados (2,4) e na experiência do cirurgião, isso parece ser pouco provável. Lembramos que o pigmento é patenteado por empresa indiana especificamente para uso ocular.…”
Section: Discussionunclassified
See 2 more Smart Citations